Marketing strategy of ecotourism in Uzbekistan and Indonesia - Yuliarni, Novia; Hurriyati, Ratih; Disman, Disman; Hendrayati, Heny; Warlina, Lia (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
This study aims to compare a marketing strategy for ecotourism in Uzbekistan and Indonesia. A marketing strategy study for ecotourism in Uzbekistan used a literature review. However, ecotourism in Indonesia used a model to examine how the ecotourism experience influences tourist satisfaction and loyalty. The authors used structural equation modeling with 400 tourists who have visited the Kawah Putih Ecotourism in West Java, Indonesia. According to study findings, Uzbekistan's ecotourism industry has a more significant positive impact on the nation's economy and society. The results show that a positive ecotourism experience in Indonesia increases tourist satisfaction and loyalty, which is essential in marketing strategy. The impact of this research is that all stakeholders in the ecotourism sector should improve marketing strategies that can increase tourist satisfaction. As a result, the tourists will repeat visits to other ecotourism destinations.